Standardization of the Pharmaceutical Substance of Lithium Salt Gamma-lactone of 2,3-dehydro-l-gulonic Acid as a Radio-sensitizing Agent - M. S. Tretyakova; S. V. Krivoshchekov; E. V. Plotnikov; E. V. Dorozhko; O. A. Voronova; M. S. Larkina; K. S. Brazovskiy; M. V. Belousov (Разработка и регистрация лекарственных средств)
Introduction. It was found that in combination with radiation exposure, high doses of lithium salts have a depressing effect on tumor leukemia cells. The selection of the appropriate anionic component makes it possible to obtain pronounced radiosensitizing properties. The lithium salt of gamma-lactone 2,3-dehydro-L-gulonic acid is a promising compound for the creation of radiosensitizing drugs. It was found that this compound exhibits high antioxidant activity among other lithium salts, while showing a pronounced radiosensitizing effect. This radiosensitizing effect is dose-dependent and manifests itself in high concentrations in combination with photon or neutron irradiation. The potential antitumor effect, due to radiosensitization, is realized through the induction of oxidative stress, which implies, first of all, an increase in cytotoxic effects on rapidly proliferating tumor cells. The obtained results provide the necessary basis for the creation of drugs with radiosensitizing activity.Aim. The aim of this work is to conduct an analytical assessment of the content of the active substance and establish the main indicators of the quality of the substance, regulated by the State Pharmacopoeia of the Russian Federation.Materials and methods. During the study, the following parameters were determined: solubility, authenticity, melting point, refractive index, specific rotation, transparency of the solution, color of the solution, pH of the solution, sulfate ash, heavy metals, impurities, water content, residual organic solvents, microbiological purity and a number of others.Results and discussion. A draft specification for the pharmaceutical substance of the lithium salt gamma-lactone 2,3-dehydro-L-gulonic acid has been developed. The optimal parameters for the control of the composition and physico-chemical characteristics and quantitative determination of the pharmaceutical substance have been determined, which is the main task for the pharmaceutical development of the drug. The results obtained make it possible to conduct a comprehensive characterization of the FS and evaluate the quality parameters of the product, which creates the basis for obtaining a dosage form and further studying the properties for creating a drug with a radiosensitizing effect.Conclusion. In the course of the work, experimental samples of the lithium salt gamma-lactone 2,3-dehydro-L-gulonic acid were synthesized and its standardization as a pharmaceutical substance was carried out in accordance with the requirements of the State Pharmacopoeia of the Russian Federation.